Як воює ІДІЛ = How ISIS Fights Військові тактики в Іраку, Сирії, Лівії та Єгипті = Military Tactics in Iraq, Syria, Libya and Egypt - Ashour, Omar (Academic Studies Press, 2023)
Based on extensive field work, this book analyzes how ISIS - a widely hated, massively outnumbered, and ludicrously outgunned organization - managed to occupy over 120 cities, towns, and villages from the Southern Philippines to Western Libya. Seeking to understand ISIS's combat effectiveness, Omar Ashour focuses on the military and tactical innovations of ISIS and their predecessors in Iraq, Syria, Libya, and Egypt. The author explains how their capacity to mix conventional military tactics with innovative guerrilla warfare and urban terrorism strategies allowed ISIS to expand and endure beyond expectations. This Ukrainian translation is supplemented by a special introduction on Russia's war against Ukraine and the ISIS tactics adoption by Russian troops (2014-2022).